Effects of essential amino acids on lipid metabolism in mice and humans. (November 2016) - Xiao, Fei; Du, Ying; Lv, Ziquan; Chen, Shanghai; Zhu, Jianmin; Sheng, Hongguang; Guo, Feifan
Abstract : Eight amino acids are considered essential for human nutrition, and three of them, including leucine, isoleucine and valine, are called as branched-chain amino acids (BCAAs). We recently discovered that dietary deficiency of any BCAA for 7 days rapidly reduces the abdominal fat mass in mice. The goal of this study was to investigate (1) whether dietary deficiency of the other five essential amino acids (EAAs), including phenylalanine, threonine, tryptophan, methionine and lysine, would produce similar effects and (2) whether an association between serum AAs and obesity was observed in humans in Chinese Han population. Similar to BCAAs deprivation, dietary deficiency of any of these five EAAs for 7 days significantly reduced abdominal fat mass, which is likely caused by increased energy expenditure. Expression of genes and proteins related to lipolysis, however, were differentially regulated by different EAAs. These results suggest a crucial role of EAAs deprivation on lipid metabolism in mice. Our human studies revealed that levels of four EAAs (leucine, isoleucine, valine and phenylalanine) were elevated in obese humans compared with those in lean controls in Chinese Han population. Based on the results obtained from mice, we speculate that these four EAAs might play important roles in human obesity.